Territory and memory as thematic meanings in neighboring sounds (2012) - Núñez-Alberca, Alejandro (2024)
This paper analyzes the process of filmic thematization present in the movie Neighboring Sounds (2012) by the Brazilian director Kleber Mendonça Filho. The objective was to identify the different elements of the mise-en-scène and the narrative features that continuously express the thematic meanings of territoriality and memory, establishing them as central axes in the construction of the story’s characters. Following a qualitative approach, the study incorporates textual analysis as it´s primary methodology to pinpoint the main formal elements and semantic associations of audiovisual language. It is concluded that the movie employs a series of narrative strategies and specific aesthetic elements to associate the presence of certain characters with different spaces and temporalities of the diegesis, marking a semantic relationship between them. Thus, the film turns spatiality and the past into the core elements to understand the characters in the story, associating itself thematically with one of the current trends in Latin American cinema such as the study of memory.